KEPATUHAN PENGGUNAAN OBAT DAN KUALITAS HIDUP PASIEN HEMODIALISA DI RS PKU MUHAMMADIYAH YOGYAKARTA PERIODE MARET 2015 - Endah Karuniawati; Woro Supadmi (Sanata Dharma University, 2016)
The adherence holds an important role that can affect the success rate of the therapy and increase the life quality of the patients. Quality of life is an ability to reflect the health in the term of physically, psychology, and socially and the satisfaction of the patients functional and control level. Research aims to understand relations compliance treatment with the quality of life can be measured by MMAS and WHOQOL questioners. The research applied descriptive, non experimental and cross-sectional methods. The aim of the research was to find out the relationship between the medication adherence and the life quality of the hemodialysis patients. The medication adherence data was gathered by MMAS (Morisky Medication Adherence Scale) and the life quality was gathered by WHOQOL (World Health Organization Quality of Life) of hemodialysis patients at PKU Muhammadiyah Yogyakarta Hospital. The research results showed that from 101 respondents the medication adherence in the level of high 58,42 %, level moderate 8 , 91 % and low 32 , 67 %.) .The quality of life of patients of the domain physical, mental, social and environmental at a high rate and low. Relations adherence the use of a drug with the quality of life of significant (p 0,005) in all the domain. Compliance the use of drugs associated with the quality of life of hemodialysis patients at PKU Muhammadiyah Yogyakarta Hospital.